Improving Follow-up Skeletal Survey Compliance in Suspected Nonaccidental Trauma Patients: What’s the FUSS About? - Gan, Tong (Pediatr Qual Saf, 2018)
INTRODUCTION: Nonaccidental trauma (NAT) victims account for a significant percentage of our pediatric trauma population. The skeletal survey (SS) and follow-up skeletal survey (FUSS) are essential in the evaluation of selected NAT patients. We identified that our clinically indicated FUSS completion rate was suboptimal. We hypothesized that implementing an intervention of postdischarge follow-up in our pediatric surgery clinic would improve FUSS completion rates. METHODS: A follow-up clinic for NAT patients was established in July 2013. A retrospective review was performed of all suspected NAT cases younger than 2 years old seen at Kentucky Children’s Hospital between November 2012 and February 2014. The study population was divided into pre (Group 1) and postintervention (Group 2). Bivariate analysis was performed. RESULTS: Group 1 consisted of 50 patients (58% male; median age, 9 months). Forty-7 (94%) had an SS; fractures were identified in 37 (74%) patients. Only 20 patients (40%) had FUSS; of those, 4 had newly identified fractures. Group 2 consisted of 52 patients (54% male; median age, 7 months). All 52 children (100%) had an SS; fractures were identified in 35 (67%) patients. Forty-seven patients (90%) had FUSS. Of those, 6 had new radiographic findings. Thirty-five patients (67%) were seen in our clinic. This improvement in FUSS (40% versus 90%) was statistically significant, P < 0.001. CONCLUSION: The decision to follow NAT patients in our clinic had significantly increased our rates of FUSS completion. This additional clinic follow-up also provided more evidence for NAT evaluation.